Studi Komparatif Pengaruh Dua Kelompok Brand Ambassador Terhadap Brand Image Telkom University - Rahadian, Sadam; Sudradjat, Ratih Hasanah; Mahdaria, Siti (Universitas Prof. Dr. Moestopo (Beragama), 2025)
The public's need for higher education is one of the factors in the increasing number of universities in Indonesia. This makes universities need to carry out marketing communications to build a positive brand image to the public and Telkom University uses brand ambassadors to build this brand image. This research aims to see the influence that Brand Ambassador Tanjidor and Brand Ambassador SMB Telkom have on Telkom University's brand image, using the dimensions of visibility, credibility, attraction and power. Meanwhile, the dimensions of brand image are strength of brand association, favorableness of brand association, and uniqueness of brand association. This research also links it to ELT communication theory. The research method used is quantitative with a comparative study type. Data collection was carried out by distributing questionnaires to 385 respondents with a population of Instagram followers @telkomuniversity and @smbtelkom. The data collection technique in this research uses a non-probability sampling technique, namely purposive sampling. The research results show that SMB Brand Ambassadors have a greater influence, both partially and simultaneously, on Telkom University's Brand Image.